Modelagem de equações estruturais na decisão de compra do consumidor em feiras livres - Nogueira, Carolina de Mattos (2019)
Demand for products from short agri-food chains, specifically free markets, is related to increased consumer demand for food quality and the impact of agriculture on the environment. This study assumes that the consumer is the final and most important link in any agri-food chain. Its objective is to analyze consumer purchase intensities in free markets in the COREDE Rio da Várzea / RS region in the light of the Planned Behavior Theory and the influencing factors in the decision making process. TPB has three beliefs - behavioral, normative, and control - and is based on the assumption that individuals make their decisions rationally and systematically use the information that is available, considering the implications of their actions before deciding whether or not to decide. not behave in a certain way. The process of consumer decision making has seven stages, each stage has several factors - cultural, social, personal and psychological - that influence the consumer's attitude, which will be analyzed in this study especially in the buying / behavior stage. The scope of the research requires an analysis involving the interaction of these two theoretical aspects, allowing from the statistical inferences to simultaneously analyze multiple variables through the use of the Structural Equation Modeling technique. The descriptive and inferential study has a quali-quantitative approach. The data collection period was carried out from March 12 to April 27, 2019. The questionnaire was applied to 195 fair market consumers using the non-probabilistic convenience sampling technique. The causal relations model of the three beliefs and the four influencing factors allowed us to test whether the seven constructs correlate. The correlation between all indicators was significant and positive, and the model with the highest significance was the Personal Factors construct model. In this model, the concern with health and quality of life were the most relevant variables, allowing us to conclude that the search for a healthier life makes consumers worry about looking for natural foods, which are found in free markets. The relationship between healthy eating influences changing habits of the population, which increasingly seeks diversified food, increasing the demand for products from family farming.